Continuous sliding mode control for gun position servo system. (March 2020) - Zhang, Gaosheng; Zhang, Zhipeng; Han, Chongwei; Gu, Shuanghao; Wang, Tianshi; Zhang, Pengfei
Abstract: With the development of military technology and changes in the war situation, modern warfare has higher requirements for the accuracy and speed of gun firing. The control performance of the gun position servo system directly affects the accuracy and speed of the gun firing. In order to improve performance of the gun, the sliding mode control is investigated for the gun position servo system. Sliding mode control has advantages of simple structure and good robustness against uncertain system parameters and disturbance. But discontinuous sign function in the classical sliding mode control method will lead to chattering of the system. To address the shortcoming of chattering in the traditional sliding mode control, a continuous sliding mode control algorithm is investigated in this paper. Finally, numerical simulations are performed to illustrate the efficiency of the theoretical results.